Uterine C-Kit positive low grade stromal sarcoma - Martin Jovitha; Ramesh Anita; Kuruvilla Sarah; Lalitha D (Indian Journal of Medical and Paediatric Oncology)
Uterine C-Kit positive stromal tumors are rare, however, there are a few cases reported in literature. A 58-year-old post menopausal lady presented with bleeding per vaginum. An abdominal examination revealed an enlarged uterus. A computed tomography scan of the abdomen and pelvis showed a large myomatous uterus, with a probable subserosal intramural and intracavitary myoma or cervical myoma in the presence of a solitary large aortocaval node, with multiple bone lesions. The biopsy taken from the uterine mass had revealed, a low-grade uterine sarcoma, which was positive for CD117. This case is presented for its rarity and management dilemma.